Sartorial creation in post-apartheid South Africa : expression of multicultural interactions - (:unkn) unknown (My University, 2013)
The transition to democracy at the end of the 1990’s and begining of the 2000’s has been a milestone for dress creation in South Africa which has enriched with new forms brought by the noticeable arrival of african fashion designers and by the development of an official fashion authority in the country : the « South African Fashion Week » and the « African Fashion International ». The thesis aims at presenting an analysis of dress creation in South Africa which reflects the multiple socio-cultural interactions developped through the country which took shape in a double fashion system : an institutionnalized fashion network, with media coverage, so « opened », a so called network in the shadow, less known, and so confidential. The thesis is attempting to answer to three main questions : How do fashion designers draw their inspiration from so-called traditionnal dresses, conveying a new post-apartheid south-african identity ? How are social and cultural tensions of South Africa reflected in dress creation ? How do the two fashion networks work ? Very few academic researches have been carried out on the specific topic of fahion design in South Africa. Besides using books and research articles, this work leans particularly on press articles and on several interviews with fashion designers and other fashion professionals during fieldworks conducted in 2009 and 2010, mainly in the city of Johannesburg and as well in CapeTown. This research couples together Sociology and Art History in order to try to understand meanings of dresses made by south african and african immigrants fashion designers, and grasp the complex relations built between actors from both fashion networks by the light of the socio-cultural context of South Africa.
Keywords: African Research